Pengaruh Taste, Kualitas Layanan dan Persepsi Harga terhadap Loyalitas Pelanggan Mie Gacoan dengan Moderasi Customer Experience - Ainisyah, Marshanda Salsabila; Mutmainah, Isbandriyati; Pranamulia, Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the factors that influence customer loyalty of Mi Gacona in Bogor City. The independent variables used in this study are Taste, Service Quality and Price Perception. The Customer Experience variable is used as a moderating variable that is thought to strengthen or weaken the influence of the Taste, Service Quality and Price Perception variables on Customer Loyalty. The population of this study is all Mie Gacoan customers in Bogor City, and the sample is determined using the accidental sampling method. The analytical method used is Multiple Linear Regression to test and analyze the influence of Taste, Service Quality and Price Perception on Loyalty, and the Moderated Regression Analysis (MRA) analysis method is used to test and analyze the ability of Customer Experience to moderate the influence of Taste, Service Quality and Price Perception on Loyalty. By using data from 119 respondents as a sample, the results of the study show that Taste and Price have a positive and significant influence on Loyalty, while Service Quality has no significant influence on Loyalty. The Customer Experience variable is proven to be able to moderate the influence of Taste, Service Quality and Price on Loyalty. These findings can be used as a reference in developing more effective marketing strategies.